Decolonizing harm reduction - Gideon Lasco (BMC, 2022)
Abstract In this essay, I show that notwithstanding the undeniable colonial origins of punitive drug policies around the world, such policies have figured in nationalist projects and populist platforms in various postcolonial states, and today they are viewed as local responses to the 'drug problem.' Instead, it is harm reduction and other efforts to reform drug policies that are seen as a colonial, or Western, imposition. I argue that to overcome such perceptions, there is a need to decolonize harm reduction alongside decolonizing drug policies. I conclude by offering recommendations toward this move, including involving Global South actors in leadership positions within the harm reduction movement, supporting pilot harm reduction programs in postcolonial states, and highlighting local scholarship.